2005
DOI: 10.1124/dmd.105.006759
|View full text |Cite
|
Sign up to set email alerts
|

EXPRESSION OF CYTOCHROMES P450, CONJUGATING ENZYMES AND NUCLEAR RECEPTORS IN HUMAN HEPATOMA HepaRG CELLS

Abstract: ABSTRACT:Most human hepatocyte cell lines lack a substantial set of liverspecific functions, especially major cytochrome P450 (P450)-related enzyme activities, making them unrepresentative of in vivo hepatocytes. We have used the HepaRG cells, derived from a human hepatocellular carcinoma, which exhibit a high differentiation pattern after 2 weeks at confluency to determine whether they could mimic human hepatocytes for drug metabolism and toxicity studies. We show that when passaged at low density, these cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

29
453
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 584 publications
(503 citation statements)
references
References 39 publications
29
453
0
1
Order By: Relevance
“…These last observations contrasted with the results of Parent et al 17 indicating that differentiated HepaRG cells preserved an immature phenotype characterized by maintenance of oval-cell markers. This discrepancy could be partly explained because DMSO exposure enhanced sev- eral liver-specific functions 18 and unexpectedly re-induced stem cell marker expression, such as CD34 in HepaRG cells as in normal adult human hepatocytes (unpublished results). Only a group of functions, including ␥GT, CEA, and c-Myc, remained relatively stable regardless of the cell differentiation status, suggesting that they could be related to cancerous markers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These last observations contrasted with the results of Parent et al 17 indicating that differentiated HepaRG cells preserved an immature phenotype characterized by maintenance of oval-cell markers. This discrepancy could be partly explained because DMSO exposure enhanced sev- eral liver-specific functions 18 and unexpectedly re-induced stem cell marker expression, such as CD34 in HepaRG cells as in normal adult human hepatocytes (unpublished results). Only a group of functions, including ␥GT, CEA, and c-Myc, remained relatively stable regardless of the cell differentiation status, suggesting that they could be related to cancerous markers.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 When optimally differentiated, HepaRG cells support HBV infection 16 and express a large panel of liver-specific genes, including those expressing drug metabolizing enzymes. 18 In this work, we analyze the possible transdifferentiation process of human liver cells using the HepaRG cell line, define the sequential expression of hepatocyte nuclear factor (HNF) family transcription factors, and identify associated signaling mechanisms involved in this process.…”
mentioning
confidence: 99%
“…HepaRG cells are a human cell line derived from a hepatocellular carcinoma that express functional liver markers, such as several cytochrome P450 (CYP) and Phase II enzymes, nuclear receptors, and membrane transporters. 18,19 When used for cytochrome P450 3A4 (CYP3A4) induction studies, HepaRG cells were found to be an excellent surrogate for primary human hepatocytes. 20 Methods for creating the 3D tissues vary from using labor-intensive single-spheroid-per-well techniques to biomaterial-reliant approaches.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to most, if not all, other available hepatic cell lines, the HepaRG cell line exhibits various liver-specific functions and is therefore proposed as a surrogate to the use of primary human hepatocytes, especially for drug metabolism and toxicity studies (Guillouzo et al, 2007;Andersson et al, 2012). Indeed, when cultured in appropriated conditions, i.e., in the presence of 2 % (vol/vol) dimethylsulfoxide (DMSO), HepaRG cells express high levels of hepatic drug detoxifying pathways, including phase 1 enzymes, such as cytochromes P-450 1A2, 2B6 and 3A4, and phase 2 enzymes such as such glutathione S-transferases A1/A2, A4 and M1 and UDPglucuronosyl transferase 1A1 (Aninat et al, 2006;Antherieu et al, 2010). Moreover, HepaRG cells exhibit notable expression of drug-sensing receptors such as pregnane X receptor and constitutive androstane receptor (Antherieu et al, 2012) and are consequently responsive to inducers of drug metabolism (Kanebratt and Andersson, 2008;Turpeinen et al, 2009).…”
Section: Introductionmentioning
confidence: 99%